Beavató gondolatok a Harry Potter újraolvasásához - Kis, Gábor (Studia Litteraria, 2019)
This essay sets out to reread the Harry Potter series as a text of initiation and draws attention to its textual self-consciousness by revealing the self-reflexive patterns of the books. It gives an analysis of The Tale of the Three Brothers and shows that the last chapters of the first book can be read as a summary of the whole series. The essay also examines how the structure of the novels mirror the traditions of alchemical initiation ceremonies by creating symbols out of the objects and phenomena of the wizarding world.